2020
DOI: 10.1017/ipm.2020.24
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and confidence of clinicians in Irish CAMHS when working with transgender youth; and the factors clinicians report will assist them in this work

Abstract: Objectives: The Health Service Executive (HSE) Quality Improvement Division (2016) report states that young people who identify as transgender are one of the highest risk groups for suicidal ideation, self-harm, and completed suicides and may require significant input in Irish Child and Adolescent Mental Health Services (CAMHS). This research represents the first exploration of CAMHS staff’s capacity within an Irish mental health service to support transgender youth by considering their knowledge about an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The findings of the study confirm the issues reported by transgender people internationally (Aylagas-Crespillo et al , 2018; Pinna et al , 2022) and in other Irish studies (Collins and Sheehan, 2004; Higgins et al , 2011; Mullen and Moane, 2013; McCann, 2015; TENI, 2017; Hodgins et al , 2020). Irish society is becoming more inclusive and more accepting of diversity, but the transgender people in our study identified limitations to this.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the study confirm the issues reported by transgender people internationally (Aylagas-Crespillo et al , 2018; Pinna et al , 2022) and in other Irish studies (Collins and Sheehan, 2004; Higgins et al , 2011; Mullen and Moane, 2013; McCann, 2015; TENI, 2017; Hodgins et al , 2020). Irish society is becoming more inclusive and more accepting of diversity, but the transgender people in our study identified limitations to this.…”
Section: Discussionsupporting
confidence: 90%
“…Whether this is available in the RoI is questioned. A review of research in RoI highlights that mental health professionals often lack specific training, are hard to access and costly and are not well prepared to work in partnership with transgender people (Collins and Sheehan, 2004; Higgins et al , 2011; Mullen and Moane, 2013; McCann, 2015; TENI, 2017; Hodgins et al , 2020). Recent developments, notably the introduction of same-sex marriage, overwhelmingly supported by a referendum, and legislation around gender diversity, are indicative of progress in Irish society.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric nurse practitioners in the USA report low levels of formal education in caring for transgender youths, despite frequently encountering them in practice 32. In Ireland, staff working within Child and Adolescent Mental Health Services report limited knowledge or experience in supporting transgender youth 33. There is an identified need for postgraduate educational interventions across healthcare disciplines 34 35…”
Section: Discussionmentioning
confidence: 99%
“… 32 In Ireland, staff working within Child and Adolescent Mental Health Services report limited knowledge or experience in supporting transgender youth. 33 There is an identified need for postgraduate educational interventions across healthcare disciplines. 34 35 …”
Section: Discussionmentioning
confidence: 99%